Air Quality Assessment of a School in an Industrialized Area of Southern Italy - Pierina Ielpo; Cristina Mangia; Gianluigi de Gennaro; Alessia Di Gilio; Jolanda Palmisani; Adelaide Dinoi; Andrea Bergomi; Valeria Comite; Paola Fermo (Applied Sciences, 2021)
In this study, simultaneous monitoring of indoor and outdoor Volatile Organic Compounds (VOCs) was carried out in a school, by both Radiello® cartridges and real-time monitors (Corvus, IonScience Ltd., Fowlmere UK). Moreover, an outdoor air quality assessment was performed with data from an air quality monitoring station (ARPA Puglia) located close to the school. In particular, VOCs, Benzene, Toluene, Ethylbenzene, and Xilenes concentrations, obtained by using Radiello® diffusive samplers, were monitored in two classrooms, two bathrooms, and outside of the school building for three weeks during winter 2019. Simultaneously, the Total VOC (TVOC) concentrations were measured by means of real-time monitors inside and outside the classroom in order to individuate the activation of sources during the sampling campaign days. The results evidence that indoor TVOC concentrations were bigger than those outdoors; this suggests the presence of indoor pollutant sources, both in the classrooms and the bathrooms. The results of our study can help the school management by the following recommendations: increasing ventilation in classrooms during school activities and after cleaning; involving students in discussions regarding the use of acrylic paints, permanent markers, perfumes and deodorants, and the limitation of smoking activities both in bathrooms and outdoor spaces.